Internet-Related Behaviors and Psychological Distress Among Schoolchildren During the COVID-19 School Hiatus - Chen, Chao-Ying; Chen, I-Hua; Pakpour, Amir H; Lin, Chung-Ying; Griffiths, Mark D (Cyberpsychology, behavior and social networking, 2021)
This study assessed the mediating roles of problematic gaming, problematic social media use, and problematic smartphone use in the associations between psychological distress and screen time use among primary school children during the school hiatus due to the outbreak of the novel coronavirus disease 2019 (COVID-19). Students ( = 2,026; mean [standard deviation] age = 10.71 years [1.07]; 1,011 [49.9 percent] girls) in Sichuan, China completed a cross-sectional online survey, and this study was approved by the ethics committee of the Hong Kong Polytechnic University (IRB ref: HSEARS20190718001). The Internet Gaming Disorder Scale-Short Form, Bergen Social Media Addiction Scale, and Smartphone Application-Based Addiction Scale were used to assess problematic gaming, social media use, and smartphone use. The Depression, Anxiety, Stress Scale-21 was used to assess distress, and an item rated on a 0-10 scale was included to assess fear of being infected by COVID-19. Fear of being infected by COVID-19 was assessed because this could be a confounding variable in the association between psychological distress and screen time use. Increased time spent on gaming, social media, and smartphones was associated with greater problematic gaming, problematic social media use, problematic smartphone use, and psychological distress, but was not associated with fear of COVID-19 infection. Mediation analyses showed that problematic gaming, problematic social media use, and problematic smartphone use were significant mediators in the association between psychological distress and increased time spent on Internet-related activities during the COVID-19 outbreak period. Children who had psychological distress during COVID-19 outbreak might have spent longer time on Internet-related activities due to the school hiatus and problematic use of Internet-related activities. Parents/caregivers are recommended to monitor their children's use of Internet while encouraging children to engage in positive activities to ease the concern of negative psychological responses during the COVID-19 pandemic.